2015
DOI: 10.1186/s12870-015-0435-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of differentially expressed genes in an orange-pericarp mutant and wild type in pummelo (Citrus grandis)

Abstract: BackgroundThe external colour of fruit is a crucial quality feature, and the external coloration of most citrus fruits is due to the accumulation of carotenoids. The molecular regulation of carotenoid biosynthesis and accumulation in pericarp is limited due to the lack of mutant. In this work, an orange-pericarp mutant (MT) which showed altered pigmentation in the pericarp was used to identify genes potentially related to the regulation of carotenoid accumulation in the pericarp.ResultsHigh Performance Liquid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 63 publications
(54 reference statements)
4
26
1
Order By: Relevance
“…Among four DEGs, The orange pericarp1 (orp1) gene encodes the tryptophan synthase b subunit with a role in tryptophan biosynthesis in maize (Wright et al, 1992). Two NAC transcription factors (NAC25 and NAM-B1) showed lower expression in the orange-pericarp mutant line of pummelo (Citrus grandis) (Guo et al, 2015). Columbamine O-methyltransferase methylates the oxygen atom of the secondary metabolites such as phenylpropanoids, flavonoids and alkaloids (Lam et al, 2007).…”
Section: Identification Of the Putative Target Of Nac7 In Protoplastsmentioning
confidence: 99%
“…Among four DEGs, The orange pericarp1 (orp1) gene encodes the tryptophan synthase b subunit with a role in tryptophan biosynthesis in maize (Wright et al, 1992). Two NAC transcription factors (NAC25 and NAM-B1) showed lower expression in the orange-pericarp mutant line of pummelo (Citrus grandis) (Guo et al, 2015). Columbamine O-methyltransferase methylates the oxygen atom of the secondary metabolites such as phenylpropanoids, flavonoids and alkaloids (Lam et al, 2007).…”
Section: Identification Of the Putative Target Of Nac7 In Protoplastsmentioning
confidence: 99%
“…The 44 WRKY-associated SSRs designed in this study may thus contribute to marker-assisted selection for phenylpropanoid pathway-related traits in jute. The MYB transcription factors are reported to be key regulators in flavonoid and anthocyanin biosynthesis pathways in rose, apple and orange (Espley et al, 2007;Guo, Yu, Xu, & Deng, 2015;Lin-Wang et al, 2010).…”
Section: Rg-specific Ssrs Associated With Phenylpropanoid Biosynthesismentioning
confidence: 99%
“…They were reported to be related to cuticle metabolism by Panikashvili et al (2010). A study on transcriptome profiling of an orange-pericarp pummelo mutant revealed that some biochemical and molecular alterations on carbon metabolism, starch and sucrose metabolism, biosynthesis of amino acids were related to the high betacarotene accumulation (Guo et al 2015). They identified top ten most DEGs involved in the regulation of carotenoid biosynthesis.…”
Section: Discussionmentioning
confidence: 99%